Sistem Mutu Pendidikan Komprehensif dan Siklus Berkelanjutan Perspektif Rusydi Ahmad Thoimah - M. Irfan; Achmad Muhlis (Education Research Center, 2025)
This study examines the conceptual foundations and operational dynamics of Quality Assurance (QA) in Islamic education by addressing the persistent gap between formal regulatory frameworks and the actual implementation of continuous quality improvement across educational institutions. Although QA has become a global imperative aligned with demands for accountability, effectiveness, and institutional competitiveness, many Islamic educational institutions still struggle to translate QA principles into an integrative, systematic, and future-oriented quality culture. Focusing on conceptual-theoretical analysis, this research aims to articulate a comprehensive understanding of QA from the perspective of Rusydi Ahmad Thoimah and to juxtapose it with major Western QA frameworks such as those proposed by Crosby, Lim, Dickinson, and ISO 9001. This qualitative study employs a library-based analytical method, combining conceptual synthesis, comparative analysis, and interpretative reading of primary and secondary literature to construct a coherent model of QA in Islamic education. The findings reveal that Thoimah emphasizes QA as a philosophical-cultural process grounded in value-based educational purposes, while Western QA models center on managerial, procedural, and preventive mechanisms designed to ensure consistency and accountability. The synthesis of both perspectives indicates that effective QA in Islamic education requires harmonizing intrinsic quality (akademik, adab, spiritual values) and extrinsic quality (stakeholder satisfaction, relevance, and global standards). The study proposes a conceptual QA model integrating input-process-output monitoring, continuous improvement, and leadership-based quality culture. These findings imply that strengthening QA in Islamic education demands not only procedural compliance but also strategic alignment, institutional commitment, and value-based quality culture to enhance long-term sustainability and competitiveness.